Preventive drugs in the last year of life of older adults with cancer: Is there room for deprescribing?. Issue 13 (25th March 2019) - Morin, Lucas; Todd, Adam; Barclay, Stephen; Wastesson, Jonas W.; Fastbom, Johan; Johnell, Kristina
Abstract : Background: The continuation of preventive drugs among older patients with advanced cancer has come under scrutiny because these drugs are unlikely to achieve their clinical benefit during the patients' remaining lifespan. Methods: A nationwide cohort study of older adults (those aged ≥65 years) with solid tumors who died between 2007 and 2013 was performed in Sweden, using routinely collected data with record linkage. The authors calculated the monthly use and cost of preventive drugs throughout the last year before the patients' death. Results: Among 151, 201 older persons who died with cancer (mean age, 81.3 years [standard deviation, 8.1 years]), the average number of drugs increased from 6.9 to 10.1 over the course of the last year before death. Preventive drugs frequently were continued until the final month of life, including antihypertensives, platelet aggregation inhibitors, anticoagulants, statins, and oral antidiabetics. Median drug costs amounted to 1482 (interquartile range [IQR], 700‐2896]) per person, including 213 (IQR, 77‐490) for preventive therapies. Compared with older adults who died with lung cancer (median drug cost, 205; IQR, 61‐523), costs for preventive drugs were higher among older adults who died with pancreatic cancer (adjusted median difference, 13; 95% confidence interval, 5‐22) or gynecological cancers (adjusted median difference, 27; 95% confidence interval, 18‐36). There was no decrease noted with regard to the cost of preventive drugs throughout the last year of life. Conclusions: Preventive drugs commonly are prescribed during the last year of life among older adults with cancer, and often are continued until the final weeks before death. Adequate deprescribing strategies are warranted to reduce the burden of drugs with limited clinical benefit near the end of life. Abstract : Preventive medications commonly are prescribed during the last year of life among older adults with cancer, and often are continued when the patient is close to death. This raises important questions because the majority of these drugs are unlikely to achieve their clinical benefit during the individual's remaining lifespan.